Structure of a eukaryotic cytoplasmic pre‐40S ribosomal subunit - Scaiola, Alain (EMBO J, 2018)
Final maturation of eukaryotic ribosomes occurs in the cytoplasm and requires the sequential removal of associated assembly factors and processing of the immature 20S pre‐RNA. Using cryo‐electron microscopy (cryo‐EM), we have determined the structure of a yeast cytoplasmic pre‐40S particle in complex with Enp1, Ltv1, Rio2, Tsr1, and Pno1 assembly factors poised to initiate final maturation. The structure reveals that the pre‐rRNA adopts a highly distorted conformation of its 3′ major and 3′ minor domains stabilized by the binding of the assembly factors. This observation is consistent with a mechanism that involves concerted release of the assembly factors orchestrated by the folding of the rRNA in the head of the pre‐40S subunit during the final stages of maturation. Our results provide a structural framework for the coordination of the final maturation events that drive a pre‐40S particle toward the mature form capable of engaging in translation.